Vitamin D receptor involves in the protection of intestinal epithelial barrier function via up-regulating SLC26A3. Issue 227 (March 2023) - Guo, Yaoyu; Li, Xiao; Geng, Chong; Song, Shuailing; Xie, Xiaoxi; Wang, Chunhui
Abstract: Background: Vitamin D receptor (VDR) and SLC26A3 (DRA) have been identified as pivotal protective factors in maintaining gut homeostasis in IBD patients. However, the specific mechanism underlying the increased intestinal susceptibility to inflammation induced by the loss of VDR and whether DRA participates in the role of VDR regulating intestinal epithelial barrier function are undefined. Aim: The current study is undertaken to elucidate the regulatory effects of VDR on DRA and VDR prevents intestinal epithelial barrier dysfunction via up-regulating the expression of DRA. Methods: WT and VDR -/- mice are used as models for intestinal epithelial response. Paracellular permeability is measured by TEER and FD-4 assays. Immunohistochemistry, immunofluorescence, qPCR and immunoblotting are performed to determine the effects of VDR and DRA on gut epithelial barrier function. Results: VDR -/- mice exhibits significant hyperpermeability of intestine with greatly decreased levels of ZO-1 and Claudin1 proteins. DRA is located on the intestinal epithelial apical membrane and is tightly modulated by VDR in vivo and in vitro via activating ERK1/2 MAPK signaling pathway. Notably, the current study for the first time demonstrates that VDR maintains intestinal epithelial barrier integrity via up-regulating DRA expression and the lack of DRA induced by VDR knockdown leads to a more susceptive condition for intestine to DSS-induced colitis. Conclusion: Our study provides evidence and deep comprehension regarding the role of VDR in modulating DRA expression in gut homeostasis and makes novel contributions to better generally understanding the links between VDR, DRA and intestinal epithelial barrier function. Highlights: The depletion of VDR impairs the intestinal epithelial barrier function by decreasing the levels of TJs. DRA located on the intestinal epithelial apical membrane is tightly modulated by VDR in vivo and in vitro. VDR maintains intestinal epithelial barrier integrity via up-regulating DRA. VDR regulates the expression of DRA via ERK1/2 MAPK signaling pathway. Loss of DRA induced by VDR knockdown is a pivotal factor of impaired intestinal barrier function in DSS-induced colitis.